Experimental methodology of socio-humanitarian knowledge: epistemological aspect - Saiganova, Veronika S. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The stages of formation and development of experimental methodology in the social sciences are discussed in the article. An interdisciplinary experiment is characterised as a type of research activity based on the integration of the methods of disciplinary science in the study of complex problems of nature and society. In social epistemology, the significance of an interdisciplinary experiment lies in its connection with social demand, the possibility of obtaining effective knowledge. Cultural and historical epistemology focuses on the interdisciplinary experiment as a process of scientific research, on the experimenting consciousness of scientists. The heuristic nature of the interdisciplinary experiment, its prognostic potential and the ability to reveal the unknown are emphasised, which is of particular importance for understanding the features of social and humanitarian cognition in modern society.